2017
DOI: 10.1007/s12975-017-0527-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluate the Efficacy and Safety of Human Urinary Kallidinogenase (RESK): Protocol for an Open-Label, Single-Arm, Multicenter Phase IV Trial for the Treatment of Acute Ischemic Stroke in Chinese Patients

Abstract: The study has registered on ClinicalTrials.gov (NCT02562183).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Studies have found that HUK can improve blood glucose utilization, promote glucose transfer, and improve insulin sensitivity. [40] This is likely to support the beneficial action of urinary kallidinogenase. Abnormal glucose metabolism is common in stroke patients and is significantly associated with the occurrence and damage of cerebral infarction.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have found that HUK can improve blood glucose utilization, promote glucose transfer, and improve insulin sensitivity. [40] This is likely to support the beneficial action of urinary kallidinogenase. Abnormal glucose metabolism is common in stroke patients and is significantly associated with the occurrence and damage of cerebral infarction.…”
Section: Discussionmentioning
confidence: 86%
“…The research included 24 trials involving 2433 patients, in which 15 trials reported that the common adverse event was transient hypotension, and there was no difference between the treatment group and control group on non-fatal intracerebral hemorrhage. A multi-center, open label, single group study has been designed and registered in ClinicalTrials.gov to reevaluate the safety and efficacy of HUK on acute ischemic stroke, and the study expects to enroll 60 sites and 2186 subjects ( 25 ).…”
Section: Results From Clinical Trialsmentioning
confidence: 99%
“…Approximately 400,000 AIS patients have been treated with uKLK1 over the past 10 years. 88 Extensive clinical literature documents the apparent efficacy of uKLK1 based on clinical research conducted in China. The regulatory approval in China was based, at least partly, upon a multicenter, randomized, double-blind, placebo-controlled trial of 446 AIS patients.…”
Section: Therapeutic Action Of Klk1 Treatment In Human Aismentioning
confidence: 99%